Public reading in early Christianity : lectors, manuscripts, and sound in the oral delivery of John 1-4 - Nässelqvist, Dan. (Novum Testamentum, Supplements, 2016)
In Public Reading in Early Christianity: Lectors, Manuscripts, and Sound in the Oral Delivery of John 1-4 Dan Nässelqvist investigates the oral delivery of New Testament writings in early Christian communities of the first two centuries C.E. He examines the role of lectors and public reading in the Greek and Roman world as well as in early Christianity. Nässelqvist introduces a method of sound analysis, which utilizes the correspondence between composition and delivery in ancient literary writings to retrieve information about oral delivery from the sound structures of the text being read aloud. Finally he applies the method of sound analysis to John 1-4 and presents the implications for our understanding of public reading and the Gospel of John.